Per l’analisi lessicale e semantica di un campione di fitonimi del napoletano - Guarino, Duilia Giada (Incontri. Rivista europea di studi italiani, 2024)
Starting from the studies of Zamboni and Beccaria on popular taxonomies, this contribution investigates the main properties and motivations of popular botanical terminology, a field of study in which different disciplines meet. The central part of the article is dedicated to the presentation and lexico-semantic analysis of a group of Neapolitan phytonyms, which exemplify the properties and motivations analyzed in the first part. As regards the most important results of this study, the sampled Neapolitan phytonyms effectively demonstrate the ambiguity, variability, heterogeneity, heterotypicality of the popular botanical lexicon, but also its internal structuring.